30 g of fibre a day: An achievable recommendation?. Issue 2 (June 2015) - Hooper, B.; Spiro, A.; Stanner, S.
Abstract The Scientific Advisory Committee on Nutrition (SACN) recently published its draft report on Carbohydrates and Health, in which new recommended intakes for fibre were proposed for children and adults, following an in‐depth review of the scientific evidence base. The recommendation for the adult population of 30 g/day, measured by the Association of Official Analytical Chemists' (AOAC) method, is somewhat higher than current recommendation and, according to intakes reported in the recent National Diet and Nutrition Survey, would require men to increase their fibre intakes by around 50% and women by 75%. This paper discusses current fibre intakes in the UK and describes the main contributors of fibre to the diet. Simple dietary modelling was carried out to investigate the feasibility of the recommendation by SACN in the context of other nutrient recommendations and food‐based guidelines. This demonstrated that it is possible to consume 30 g of AOAC fibre a day in the context of a healthy diet that meets other dietary recommendations if all meals are based on starchy foods (including mainly wholegrain options and potatoes with their skins), high fibre snacks are selected and the diet is rich in fruit and vegetables (around 8 portions daily). Barriers to meeting the recommendation are considered, including the negative consumer perceptions of starchy foods and a lack of awareness regarding the health benefits of fibre, particularly those beyond bowel health. Labelling regulations may pose further challenges, as there is not an agreed definition for 'wholegrain' and the European Food Safety Authority (EFSA) has concluded that there is, as yet, insufficient evidence to warrant an official health claim for dietary fibre (as a general food ingredient). Although feasible in the context of other dietary guidelines, the required dietary pattern to achieve 30 g of AOAC fibre a day is not reflective of average diets in the UK. Achieving this population recommendation will therefore be a considerable challenge. Co‐operation and collaboration is likely to be required from a number of stakeholders including the food industry, health professionals and regulatory bodies to raise awareness of the benefits of dietary fibre and encourage greater consumption of higher fibre foods. Innovative high fibre ingredients may also be needed to make it easier for consumers to boost their fibre intakes.